Driven Camshaft Power Mechanism of the Vehicle Diesel Engine Fuel Pump - Ðœoroz, Mykola; Korol, Serhii; Chernenko, Serhii; Boiko, Yurii; Vasylkovskyi, Oleksii (International Journal of Engineering and Technology, 2018)
The article deals with the actual problem associated with poor-quality operation of vehicle engines with incomplete loading and operation at partial high-speed modes. It is shown that such engine operating modes make up the bulk of the time, especially when the vehicle operates in urban conditions. Poor engine performance in these modes results in decline in fuel economy and environmental performance. To improve the technical performance of diesel engines, a device is proposed that allows control the uneven rotation of camshaft of vehicle diesel fuel pump. The kinematic schemes of the angular velocity transducers for fuel pump camshaft power mechanism, the kinematic and power drive calculation method are developed.Â Â
Keywords: Camshaft; Diesel Engine; Fuel Pump; Kinematic Diagram; Partial Modes of Diesel Engine Operation.